Sub-Synchronous Interaction Damping Control for DFIG Wind Turbines - Leon, Enrique Andres (2015)
This paper presents a damping control to mitigate sub-synchronous interactions (SSI) in doubly-fed induction generator (DFIG) wind turbines connected to series-compensated lines. This issue has gained attention due to the recent SSI phenomena reported in DFIG wind farms located near series capacitors. Two approaches which add a supplementary damping control signal are compared: one of them, integrated to the grid-side converter, and the other one, to the rotor-side converter. The SSI damping controls are designed using a multi-input multi-output state-space methodology. This allows to easily tune a high performance controller using several measurements and control inputs. Smalland large-signal stability analyses, robustness aspects, impact of the supplementary controls on the system modes, and influence of different operating conditions on the SSI are also discussed. The obtained results show that the supplementary control is able to properly damp the sub-synchronous oscillations of DFIG wind turbines by updating the existing DFIG control systems without the inclusion of expensive additional damping devices, and reducing the risk of wind generation tripping.